Effect of Insurance Type on Postoperative Tympanostomy Tube Follow-up. (June 2022) - Patel, Terral A.; McCoy, Jennifer L.; Belsky, Michael A.; Sim, Edward S.; Konanur, Anisha; Yan, Annie; Jabbour, Noel; Padia, Reema
Objective: Bilateral myringotomy with tube insertion (BMT) is a common procedure performed in children. Appropriate follow-up is necessary to ensure management of postoperative sequalae. The objectives are to investigate (1) the relationship between insurance type and postoperative follow-up attendance and (2) the effect of follow-up on need for further care after BMT. Study Design: Retrospective cohort study. Setting: The study included patients <3 years of age undergoing BMT for recurrent acute otitis media at a tertiary care children's hospital within a single year and followed for 3 years. Patients were excluded if they had received a prior BMT; underwent a concurrent otolaryngologic procedure; or had a syndromic diagnosis, craniofacial abnormality, or any significant cardiac or respiratory comorbidity. Methods: Number of follow-up appointments, demographics, socioeconomic status, and postoperative outcomes were analyzed. Results: A total of 734 patients were included with mean (SD) age of 1.4 years (0.50). The majority of patients had private insurance (520/734, 70.8%). Patients with public insurance attended fewer postoperative appointments (1.5 vs 1.8, P < .001) and had a higher incidence of BMT-related emergency department (ED) visits (10.3% vs 3.8%, P = .001). There was no significance found when different insurance providers were compared. An adjusted multivariate regression analysis showed that patients with private insurance were more likely to attend postoperative appointments (odds ratio, 3.52 [95% CI, 2.12-5.82]; P < .001) and less likely to have a BMT-related ED visit (odds ratio, 0.42 [95% CI, 0.20-0.89]; P = .024). Conclusion: Insurance type is related to outcomes after the treatment of recurrent acute otitis media with BMT. Future studies that survey individuals will help identify barriers that contribute to patient absence at follow-ups and need for subsequent ED visits.